Analysis of the Importance of Sacroiliac Joint Fractures as a Prognostic Factor of the Patients with Pelvic Fractures - Yeon-Uk Ju; Jun-Min Cho; Nam-Ryeol Kim; Kyung-Bum Lee; Jin-Kak Kim; Jong-Keon Oh (Journal of Trauma and Injury)
Purpose The diagnosis of pelvic fractures pattern has become to be essential in the decision making of treatment modality and reducing morbidity and mortality in multiple trauma patients. Sacroiliac joint (SIJ) disruption can cause life-threatening massive arterial bleeding. This study aimed to determine a method of predicting the prognosis and treatment direction with pelvis X-ray alone in the emergency room. We investigated whether SIJ disruption can be used alone as a poor prognostic factor. Methods We analyzed the medical records and radiologic examination results of 167 patients with pelvic fractures from January 1, 2015 to December 31, 2016 retrospectively. Patients with pathologic fractures, thoraco-abdominal bleeding, and acetabulum fractures and pediatric patients (n=63) were excluded. Factors related to the clinical manifestations and treatments, such as transfusion and surgery, were statistically compared. Results The cross-sectional analysis showed that there was no correlation between SIJ injury and sex; there were statistically significant relationships between occurrences of shock, conjoined fractures, transfusion, and surgeries. The hospitalization period and partial thromboplastin time and prothrombin time values increased. The logistic regression analysis showed that when an SIJ injury occurred, blood transfusion and hypotension possibilities increased. Conclusions When pelvic fractures occur near the SIJ, blood transfusion and shock possibilities increase. Physicians must be aware of the high severity and poor prognosis of such fractures when these are diagnosed in the emergency room. And furthermore, the physician has to predict and prepare the intensive care and multidisciplinary approaches.